Pemetaan Kemampuan Menyelesaikan Soal Gelombang Bunyi Berdasarkan Teori Polya Pada Peserta Didik Di SMA Katolik Sint Carolus - Ingki Adetrisna Lumu Kadja; Claudia M. M. Maing; Maria Ursula Jawa Mukin (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2023)
The purpose of this study was to determine the ability of participants in the process of solving problems of sound wave material based on Polya's theory. Polya's theory describes four stages that are carried out in the process of solving a problem, namely understanding the problem, planning the problem solving, carrying out the problem solving and checking the results. In order to obtain data on the students' ability to solve a problem, the research used the testing technique. Tests were given to 19 students in the form of questions in the form of descriptions with a total of five question numbers. The results of the data analysis show data on the percentage of students' abilities for four aspects based on Polya's theory, which are classified based on high, medium and low criteria. The results of the percentage of students' abilities at the stage of understanding the problem obtained the results that 15.79% were in the high category, 68.42% were in the medium category and 15.79% were in the low category. The stage of planning problem solving obtained results 36.84% were in the high category and the medium category and 26.32% were in the low category. The stage of implementing problem solving obtained 100% results in the low category and the last stage, which was checking the results, obtained 5.26% results in the high category, 5.26% were in the medium category and 89.47% were in the low category. From the results of the data analysis obtained, it can be seen that the percentage of students' abilities from very low to high is successively in the stage of carrying out problem solving, in the stage of re-examining the results, in the stage of planning problem solving and in the stage of understanding the problem.